Status of Sequestered Organic Carbon in the Soils under Different Vegetation Covers - Negi, S. S.; Gupta, M. K. (Indian Forester, 2013)
Estimation of SOC pool under different vegetation covers was conducted in Almora district of Uttarakhand state in two land uses viz. forests where soil organic carbon pool was estimated in Deodar (Cedrus deodara), Quercus (Quercus leucotrichophora), Sal (Shorea robusta), Chir (Pinus roxburghii) and miscellaneous forests and under horticulture land use where SOC pool was estimated in apple orchards. Maximum SOC pool was observed in the soils under Deodar forest (114.36 t ha-1) followed by Quercus (91.77 t ha-1), Sal (61.51 t ha-1), Chir (54. 18 t ha-1) and the least was under miscellaneous (24.68 t ha-1). Subset for Î±= 0.05 indicate that Deodar stands separately (a), Quercus stand separately (b) Sal and Chir were together (c) and miscellaneous forest was also in separate SOC pool (d). SOC pool in soils under apple orchards was 61.99 t ha-1 . On an average, forests in Almora district have 73.76 t ha-1 SOC pool in the soils. All the forests of the districts have 1,74,20,939.95 tones (17.42 million tons) SOC store in the soils. In the district 1.26 million tons SOC pool was estimated in the soils under horticulture land use system.